Sulfate sulfur isotopes and major ion chemistry reveal that pyrite oxidation counteracts CO2 drawdown from silicate weathering in the Langtang-Trisuli-Narayani River system, Nepal Himalaya. (1st February 2021) - Kemeny, P.C.; Lopez, G.I.; Dalleska, N.F.; Torres, M.; Burke, A.; Bhatt, M.P.; West, A.J.; Hartmann, J.; Adkins, J.F.
Highlights: δ 34 SSO4 and major ions are set by lithology principally and seasonality secondarily. Sulfide and Sorg oxidation source 62–101% of SO4 2− in Langtang-Trisuli-Narayani. The fraction of H2 SO4 -driven weathering varies seasonally with system hydrology. Narayani catchment weathering does not reduce pCO2 on timescales >5 kyr and <10 Myr. Abstract: Drawdown of atmospheric carbon dioxide (CO2 ) due to silicate weathering in the Himalaya has previously been implicated in Cenozoic cooling. However, over timescales shorter than that of the removal of marine sulfate (SO4 2− ), the oxidation of pyrite (FeS2 ) in weathering systems can counteract the alkalinity flux of silicate weathering and modulate pCO2 . Here we present evidence from 34 S/ 32 S isotope ratios in dissolved SO4 2− (δ 34 SSO4 ), together with dissolved major ion concentrations, that reveals FeS2 oxidation throughout the Langtang-Trisuli-Narayani River system of the Nepal Himalaya. River water samples were collected monthly to bimonthly throughout 2011 from 16 sites ranging from the Lirung Glacier catchment through the Narayani River floodplain. This sampling transect begins in the High Himalayan Crystalline (HHC) formation and passes through the Lesser Himalayan (LH) formation with upstream influences from the Tethyn Sedimentary Series (TSS). Average δ 34 SSO4 in the Lirung Glacier outlet is 3.6‰, increases downstream to 6.3‰ near the confluence with the Bhote Kosi, and finally declines to −2.6‰ in the lower elevation sites. Using new measurements of major ion concentrations, inversion shows 62–101% of river SO4 2− is derived from the oxidation of sulfide minerals and/or organic sulfur, with the former process likely dominant. The fraction of H2 SO4 -driven weathering is seasonally variable and lower during the monsoon season, attributable to seasonal changes in the relative influence of shallow and deep flow paths with distinct residence times. Inversion results indicate that the primary control on δ 34 SSO4 is lithologically variable isotope composition, with the expressed δ 34 S value for the LH and TSS formations (median values −7.0–0.0‰ in 80% of samples) lower than that in the HHC (median values 1.7–6.2‰ in 80% of samples). Overall, our analysis indicates that FeS2 oxidation counteracts much of the alkalinity flux from silicate weathering throughout the Narayani River system such that weathering along the sampled transect exerts minimal impact on pCO2 over timescales >5–10 kyr and <10 Myr. Moreover, reanalysis of prior datasets suggests that our findings are applicable more widely across several of the frontal Himalayan drainages.